PENINGKATAN KETERAMPILAN BERBICARA SISWA MENGGUNAKAN MEDIA AUDIOVISUAL DI KELAS V SEKOLAH DASAR NEGERI - Rizka Dwiki Mutiari; Siti Halidjah; Sugiyono Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis study aims to describe the improvement of speech skill using audiovisual media. The research method used is descriptive method while the form of research is a classroom action research with the nature of collaborative research. Place in research took in the country’s basic school 36 Pontianak Selatan. Subjek in research that is the teacher as a collaborator and student grade VA amounted to twenty people.Data collection techniques used are techniques of observation and documents. This research is done as much as 3 cycles with each.The result of the research are (1) the ability of teachers to design the learning cycle i have average 2.80, category average, cycle ii average 3,38 good category and cycle iii 3,66 excellent category. (2) the ability of teachers to implement learning cycle i has average value of 2.65 categories enough ,cycle ii average 3,44 categorized good and iii cycle average 3,79 category is very good. Then on the result of students’ speaking skill on the first cycle of the average score of 58.58 on the second cycle of the average score of 72,73 students in the third cycle student average score 82.31 It can be concluded that using audiovisual media in learning Indonesian language. Keywords : Improvement, Speaking skill, Audiovisual Media